Validation of the van der Waals broadening method for the determination of gas temperature in microwave discharges sustained in argon–neon mixtures. (February 2018) - Muñoz, J.; Rincón, R.; Melero, C.; Dimitrijević, M.S.; González, C.; Calzada, M.D.
Highlights: Van der Waals broadening used to calculate gas temperature in Ar–Ne plasmas. Calculations consider the influence of both Ar and Ne perturbing atoms. Results show the method is valid for neon concentrations ranging from 0 to 90%. Abstract: Gas temperature is a key parameter to understand the processes that take place in a plasma because this temperature is related to the energy of the heavy plasmas particles which participate in the atomization of molecules and the formation of radicals from the substances introduced into the discharges. The method for the measurement of gas temperature in argon-helium plasma at atmospheric pressure, using the van der Waals broadening of spectral atomic lines, is adapted for the case of argon–neon mixtures. The Ar I lines 425.9 nm and 603.2 nm are determined as recommendable for such measurements, especially when the use of OH radicals is difficult or the contribution of these radicals to the plasma pollution is to be avoided. Graphical abstract: